Binary aromatic self-assembled monolayers: electrostatic properties and charge tunneling rates across the molecular framework - Asyuda, Andika; Wan, Xianglong; Zharnikov, Michael (Physical chemistry, chemical physics, 2020)
A series of single-component and binary SAMs composed of non-substituted (H-BPT) and fluorine-substituted (F-BPT) mercaptobiphenyls on Au(111) was studied in the context of their structure, composition, electrostatic properties, and charge tunneling rates in molecular junctions. All SAMs were found to be well-defined and densely packed, with all molecules bound to the substrate by the thiolate anchor and orientated upright with respect to the substrate. The relative composition of the binary SAMs turned out to be close to the relative contents of both molecules in the solutions from which these SAMs were formed. The work function of the binary SAMs can be varied in a gradual and controlled fashion between the ultimate values for the single-component films, viz. ∼4.3 eV and ∼5.2 eV. The extent of the electrostatic effects in photoemission is small, affecting predominantly the apparent binding energy of the terminal fluorine atoms, which is explained by the strong spatial confinement of the step in the electrostatic potential at the SAM-ambient interface. The charge tunneling rate across the molecular framework is noticeably (by about an order of magnitude) higher for the H-BPT SAM than for the F-BPT monolayer, in good agreement with the literature data. The tunneling rates for the mixed SAM are intermediate to those of the single-component films, varying in a gradual fashion with the SAM composition between the respective ultimate values.
Gesehen am 19.03.2021